(untitled) (Ágora Journal, 2022)
Social equality and non-discrimination are guarantees assumed as human rights, however in Brazil hostility and necropolitics towards Lesbians, Gays, Bisexuals, Transvestites and Transsexuals - LGBT are commonplace. A situation that intensifies with the resurgence of neoconservatism, also responsible for the dismantling of public policies related to this community. In this sense, this article aims to discursively analyze the ordinary municipal laws related to demands, public problems, and LGBT rights in Juazeiro do Norte, a municipality in the Metropolitan Region of Cariri in the State of Ceará. To this end, an investigation was carried out on documents in the public domain directly related to LGBT demands/existences in the defined time frame from 2000 to 2022. Eighteen directly related laws were analyzed, which were categorized in the areas of public policies: public security; social participation; education; HIV/Aids; and social assistance. It is concluded that the municipality has different LGBT legal frameworks, however, it also faces contradictions and political-institutional obstacles to the realization of the rights of this social group.